EDUKASI MANAJEMEN SEHAT ALA SANTRI MELALUI PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Makiah, Makiah; Mohammad Ziad , Anwar (STIE PGRI Dewantara Jombang, 2024)
Abstract Islamic boarding schools as educational institutions that focus on religion, have a very large share in educating the lives of the nation's children. Most boarding schools to date still have classic problems related to sanitation, hygiene. The cleanliness and health of students in boarding schools are still not prioritized, causing skin diseases that are easily transmitted to students. In supporting the lives of students in boarding schools, it is important for students to maintain the cleanliness of the pesantren environment and maintain personal hygiene, namely by implementing Clean and Healthy Living Behavior (PHBS). Providing education through the delivery of healthy management materials in the style of santri through the application of PHBS begins with the preparation, implementation and evaluation stages. This activity involved 100 santriwan and santriwati SMP-IT Pondok Pesantren Asshohwah Al-Islamiyah, Gerung, West Lombok Regency, West Nusa Tenggara. Delivery of material through counseling, mentoring, and guidance to students on how to maintain cleanliness and health through PHBS. The evaluation stage is carried out by assessing the students' understanding of the material that has been delivered. This service activity is not enough to provide education, but there needs to be a follow-up observation and monitoring of the implementation of school PHBS so that students really maintain cleanliness and health, thus obtaining healthy students for a strong Indonesia, from students for the country.